Growth and highly efficient third harmonic generation of ammonium dihydrogen phosphate crystals. Issue 40 (6th April 2016) - Feng, Xi; Zhu, Lili; Li, Fuquan; Wang, Fang; Han, Wei; Wang, Zhengping; Zhu, Qihua; Sun, Xun
Abstract : ADP crystals were grown, and their optical properties including third harmonic generation were measured. Abstract : The growth of ammonium dihydrogen phosphate (ADP) crystals and their optical properties were studied. ADP crystals were first obtained using a potassium dihydrogen phosphate (KDP) seed crystal. Then single ADP crystal was obtained by using ADP plate seed and tetragonal pyramid seed, respectively. The optical properties including transmittance, refractive index, nonlinear optical coefficient and laser-induced damage threshold were also reported and suggested that ADP crystals are a promising alternative to KDP crystals in inertial confinement fusion. The third harmonic generation efficiency was investigated systematically, and all of the samples achieved efficiencies higher than 50%.